Transcriptome and Proteome Alternation With Resistance to Bacillus thuringiensis Cry1Ah Toxin in Ostrinia furnacalis - Shabbir, Muhammad Zeeshan; Zhang, Tiantao; Wang, Zhenying; He, Kanglai (Frontiers in Physiology, 2019)
Background: Asian corn borer (ACB), Ostrinia furnacalis can develop resistance to transgenic Bacillus thuringiensis (Bt) maize expressing Cry1Ah-toxin. However, the mechanisms that regulate the resistance of ACB to Cry1Ah-toxin are unknown. Objective: In order to understand the molecular basis of the Cry1Ah-toxin resistance in ACB, “omics” analyses were performed to examine the difference between Cry1Ah-resistant (ACB-AhR) and susceptible (ACB-BtS) strains of ACB at both transcriptional and translational levels. Results: A total of 7,007 differentially expressed genes (DEGs) and 182 differentially expressed proteins (DEPs) were identified between ACB-AhR and ACB-BtS and 90 genes had simultaneous transcription and translation profiles. Down-regulated genes associated with Cry1Ah resistance included aminopeptidase N, ABCC3, DIMBOA-induced cytochrome P450, alkaline phosphatase, glutathione S-transferase, cadherin-like protein, and V-ATPase. Whereas, anti-stress genes, such as heat shock protein 70 and carboxylesterase were up-regulated in ACB-AhR, displaying that a higher proportion of genes/proteins related to resistance was down-regulated compared to up-regulated. The Kyoto encyclopedia of genes and genomes (KEGG) analysis mapped 578 and 29 DEGs and DEPs, to 27 and 10 pathways, respectively (P < 0.05). Furthermore, real-time quantitative (qRT-PCR) results based on relative expression levels of randomly selected genes confirmed the “omics” response. Conclusion: Despite the previous studies, this is the first combination of a study using RNA-Seq and iTRAQ approaches on Cry1Ah-toxin binding, which led to the identification of longer length of unigenes in ACB. The DEGs and DEPs results are valuable for further clarifying Cry1Ah-mediated resistance.